Times of Occupation: Experiences, Faces and Spaces in Europe at War (1936-1945). An Introduction - Pérez-Olivares, Alejandro (Hispania Nova, 2021)
Dossier coordinated by Alejandro Pérez-Olivares.This text introduces the contributions that make up this special issue called ‘Times of occupation: Experiences, Faces and Spaces in Europe at war (1936-1945)’. In this sense, it focuses on the main questions that allow us to understand the occupations during the ‘total war era’, a transnational reality which is addressed thanks to different case studies in Spain, the Netherlands and France.
Keywords: occupations; total war; “european civil war”; transnational history